A TM03 mode reduced side lobe high‐gain printed antenna array in K band for UDN and IoT applications in 5G. Issue 11 (9th September 2020) - Pal, Joydeep; Patra, Kaushik; Gupta, Bhaskar
Abstract: A single layer simple feed reduced side lobe gain‐enhanced microstrip antenna array using higher‐order modes is analyzed and designed in this work. The relationship between the relative magnitude of equivalent magnetic currents and directivity are studied. Modal analysis for rectangular patch is considered for broadside and non‐broadside radiation. Comparative investigations on antenna radiation and impedance characteristics for fundamental and higher‐order modes are presented. It is observed that an array can be designed to operate in TM03 mode for enhanced gain with broadside radiation. Parametric optimization is carried out to attain low side lobe level. The proposed theory is validated by designing and fabricating a single layer single feed 2 × 2 microstrip patch array in the K band operating in TM03 mode. The simulated and measured realized gain of the fabricated TM03 mode array is 16.1 and 15.5 dBi, respectively, at 22 GHz with consistent broadside radiation pattern and linear polarization.